Actual and perceived monetary policy rules in a dynamic equilibrium model of the euro area - Mika Kortelainen (Bank of Finland, 2001)
We present a dynamic general equilibrium model with some nominal rigidities and calibrate it to euro area data.The most important features of the model include consumption/saving decisions according to Blanchard's stochastic lifetimes approach; valuation of private financial wealth according to the present value of capital income; overlapping Calvo wage contracts in the labour market; and a neoclassical supply side with Cobb-Douglas technology.The model is developed for use in analysing differences between perceived and actual monetary policy rules, which is then done as a means of evaluating the macroeconomic benefits of credibility in monetary policy.General properties of the model are analysed with a variety of simulation experiments.
URN:NBN:fi:bof-20140807107
Keywords: 330; EDGE; rational expectation; DGE models; nominal rigidites